Influência do estado nutricional pré-operatório na morbimortalidade de pacientes submetidos à cirurgia cardíaca - Silva, Juliana Teixeira da (2012)
Everybody agree that the pre-operative nutritional condition of large surgeries patients, mainly those envolving intestinal tract, influence their clinical evolution. However, studies that evaluate the impact of pre-operative nutritional status in the morbimortality of heart surgery patients are rare. Objective: Know the influence of pre-operative nutritional status in the morbimortality of heart surgery patients. Methods: This is an observational, descriptive and prospective study, based on a peri-operative monitoring heart surgery patients in a hospital of Aracaju-SE city. The data collect was divided in three steps: 1 step pre-operative variables collect (age, genre, co-morbidity presence, euro-score determination, body mass index, tricipital skin fold fitness percentage, arm circumference and arm muscle circumference, and waist circumference); 2 step post-operative data collect (death and infectious complications presence, or not); 3 step The post-operative monitoring extended before hospital check out by a weekly phone call until 30 days after. Results: The sample was formed by 173 individuals of both sexes, with average age (57,4±10,5 years), most of male sex (59,5%). The most frequent surgical procedure was the coronary artery bypass graft surgery, that was performed in 116 patients (67%). The mortality tax was 16,2% and the average time of hospital stand was 8 days. 58,8% of the individuals presented overweight/obesity diagnosis determined by body mass index and more than 30% of patients presented muscular mass reservations, expressed by arm circumference and arm muscle circumference fitness percentage, below normality rate (34,7% and 32,4%, respectively). The multivariable analysis didn t show a significant association (p=0,13) of death variable with antropometric variables set, however the effect dimension (eta2parcial = 0,050) and the power (Power = 0,592) were low. A significant association was shown between body mass index (p=0,02), the waist circumference (p=0,001), the arm circumference fitness percentage fitness (p=0,02) and post-operative complications occurrence (p=0,01), with dimension effect between small and large intensity. Conclusion: The malnutrition status influence the increase of post-operative complications occurrence, strongly associated with noninfectious complications incidence in this patients group.